2018
DOI: 10.3390/app9010037
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of Efficient Electromagnetic Interference Shielding Polymer Composites via Fused Deposition Modeling

Abstract: Acrylonitrile–butadiene–styrene (ABS) filled with 6 wt.% of multi-walled carbon nanotubes and graphene nanoplatelets was extruded in filaments and additively manufactured via fused deposition modeling (FDM). The electrical conductivity and electromagnetic interference shielding efficiency (EMI SE) in the frequency range between 8.2 and 12.4 GHz of the resulting 3D samples were assessed. For comparison purposes, compression molded samples of the same composition were investigated. Electrical conductivity of abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…[2][3][4][5][6] Recently, the use of graphene, and other carbon-based fillers, as filler material in ME filaments have attracted great interest as they can be used to impart a range of enhancements beyond mechanical properties. For example, addition of graphene and carbon nanofibres can convert insulating materials like poly(acrylonitrilebutadiene-styrene) (ABS), [7][8][9] poly(lactic acid) (PLA), 10,11 polystyrene (PS), 12 and linear low-density polyethylene (LLDPE) 13 into electrically conductive filaments.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Recently, the use of graphene, and other carbon-based fillers, as filler material in ME filaments have attracted great interest as they can be used to impart a range of enhancements beyond mechanical properties. For example, addition of graphene and carbon nanofibres can convert insulating materials like poly(acrylonitrilebutadiene-styrene) (ABS), [7][8][9] poly(lactic acid) (PLA), 10,11 polystyrene (PS), 12 and linear low-density polyethylene (LLDPE) 13 into electrically conductive filaments.…”
Section: Introductionmentioning
confidence: 99%
“…An selected composition (Dul et al, 2018b;Ecco et al, 2018) of 6 wt.% of CNT were first melt blended with ABS matrix through a Thermo-Haake Polylab Rheomix counter-rotating internal mixer at a temperature of 190 • C and rotor speed of 90 rpm for 15 min. The resulting material was granulated in a Piovan grinder Model RN 166 and grinded pieces with average size of 2.1 ± 0.6 mm) were used to feed a Thermo Haake PTW16 intermeshing corotating twin screw extruder (screw diameter = 16 mm; L/D ratio = 25; nozzle die diameter 1.80 mm).…”
Section: Production Of Filament Nanocompositesmentioning
confidence: 99%
“…In our previous works, highly conductive ABS/CNT nanocomposites with 6 wt.% of nanofillers were successfully 3Dprinted through FFF process and their extensive characterization including tensile, thermal and electrical properties was reported (Dul et al, 2018a). The composition percentage of 6 wt.% of CNT was properly selected in the tested range 2-8% wt.%, as an adequate compromise between the improvement of some properties after addition of the filler, and the correspondent reduction of composite processability, as evidenced by the critical decrease of melt flow (Dul et al, 2018b) and melt viscosity (Ecco et al, 2018). Electrical and magnetic properties of both graphene and CNT nanocomposites were studied and compared in view of EMI-SE applications (Ecco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the electrical conductivity obtained in 3D printed parts was lower than that of the filament prior to printing, the values were in the order of other reported parts manufactured by extrusion-based AM, as can be corroborated from data included in Table 4. It has been demonstrated that the electrical conductivity of parts obtained by extrusion-based AM is reduced at least one order of magnitude with respect to conventional methods as compression molding (CM) [36]. Another issue to consider is the anisotropy of the 3D printed parts, as there is preferential orientation of the electrically conductive nanoparticles when the composite pass through the nozzle tip.…”
Section: Influence Of 3d Printing Operational Parameters On the Electmentioning
confidence: 99%